Let's solve your equation step-by-step.
<span><span><span><span>4<span>x^2</span></span>+<span>28x</span></span>−32</span>=0
</span>Step 1: Factor left side of equation.
<span><span><span>4<span>(<span>x−1</span>)</span></span><span>(<span>x+8</span>)</span></span>=0
</span>Step 2: Set factors equal to 0.
<span><span><span>x−1</span>=<span><span><span>0<span> or </span></span>x</span>+8</span></span>=0
</span><span><span>x=<span><span>1<span> or </span></span>x</span></span>=<span>−<span>8</span></span></span>
Answer:
The answer is 11a+3
Step-by-step explanation:
Simplify the terms.
8a+3+5a-2a
Combine like terms.
8a+5a-2a=11
11a+3
Answer:
First point - (0,-2)
second - (2,-1)
Third - ( 4, 0)
Step-by-step explanation:
Answer:
Step-by-step explanation:
false
Answer: B. 3x + 1/5
tom's pencil is longer than Ellen's pencil:
5x + 2/5 - (2x + 1/5) = 5x - 2x + 2/5 - 1/5 = 3x + 1/5 (cm)
Step-by-step explanation: